Targeting shared pathways in tauopathies and age-related macular degeneration: implications for novel therapies - Rinaldi, Michele; Pezone, Antonio; Quadrini, Gaia Italia; Abbadessa, Gianmarco; Laezza, Maria Paola; Passaro, Maria Laura; Porcellini, Antonio; Costagliola, Ciro (Frontiers in Aging Neuroscience, 2024)
The intricate parallels in structure and function between the human retina and the central nervous system designate the retina as a prospective avenue for understanding brain-related processes. This review extensively explores the shared physiopathological mechanisms connecting AMD and proteinopathies, with a specific focus on tauopathies. The pivotal involvement of oxidative stress and cellular senescence emerges as key drivers of pathogenesis in both conditions. Uncovering these shared elements not only has the potential to enhance our understanding of intricate neurodegenerative diseases but also sets the stage for pioneering therapeutic approaches in AMD.